Case Report: Exploring delayed hyperprogressive disease: a case study of post-immunotherapy in lung cancer - Zhou, Jie; Cao, Kexin; Wei, Jin-Xia; Wang, Biao; Li, Meng-Jie; Zhu, Jian; Ai, Guo-Ping; Liu, Qiu-Lian (Frontiers in Immunology, 2025)
BackgroundRecent studies have shown that immunotherapy improves survival outcomes for patients with a late staged cancer. However, in a small number of cases do not benefit from this treatment and instead experience rapid tumor progression, known as hyperprogressive disease (HPD). Currently, HPD is provisionally defined as occurring within two months of receiving immunotherapy. Is HPD that occurs after two months associated with immunotherapy? The existing literature does not provide an answer.Case presentationA 59-year-old woman was diagnosed with unresectable squamous cell carcinoma of the lung. She received four months (6 cycles) of chemotherapy with albumin-bound paclitaxel and cisplatin, along with immunotherapy using Camrelizumab. After treatment, the lesion in the patient’s lung were significantly reduced. However, because the tumor did not disappear and due to the limitations dose of the chemotherapy drugs using for body, the patient turned to receive stereotactic radiation therapy (2 Gy per fraction). After 10 fractions of radiotherapy, the lesion in the patient’s lung significantly increased. The enlarged lesion was pathologically analyzed through a percutaneous lung biopsy and was confirmed to be squamous cell carcinoma. Following the cessation of radiotherapy, four cycles of targeted segment arterial chemoembolization resulted in another significant reduction in the lung lesion.ConclusionsThis report is the first to present HPD after 5 months of immunotherapy, marking the longest recorded occurrence of this phenomenon. This particular case of post-immunotherapy HPD achieved satisfactory results through targeted segment arterial chemoembolization, offering a potential approach for managing this side effect.